2021
DOI: 10.32722/acc.v8i1.3876
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Sikap, Norma Subjektif, Dan Persepsi Risiko Terhadap Minat Bertransaksi Menggunakan Aplikasi Fintech

Abstract: This research aims to determine the effect of attitude, subjective norm, and perceived risk on transaction interest using fintech application. Respondent use were students of the Jakarta State Polytechnic Accounting Department as many as 100 respondents. The technique in sampling uses the purposive sampling method. Analysis of the data used in this research is multiple linear regression analysis using SPSS version 26. The results of this research indicate the attitude have a positive and significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of Hypothesis 8 test showed that subjective norms had a positive and significant effect on interest in using paylater. The results of this study are in accordance with the research of Rahmatika and Fajar (2019) and Dharmawan et al (2021) which found that there is a positive influence of subjective norms on interest in using financial technology products. This explains that a person's interest in using paylater is strongly influenced by the people around him such as family, relatives, and people who are important and influential to him.…”
Section: Recommendationssupporting
confidence: 90%
“…The results of Hypothesis 8 test showed that subjective norms had a positive and significant effect on interest in using paylater. The results of this study are in accordance with the research of Rahmatika and Fajar (2019) and Dharmawan et al (2021) which found that there is a positive influence of subjective norms on interest in using financial technology products. This explains that a person's interest in using paylater is strongly influenced by the people around him such as family, relatives, and people who are important and influential to him.…”
Section: Recommendationssupporting
confidence: 90%
“…The result signifies that consumers' perceived benefits will affect consumer attitudes towards fintech use. Dharmawan et al (2021) discovered, utilizing a sample of fintech user data in Jakarta, that risk perception substantially impacted interest in fintech use. The higher the benefits, the more positive attitude of consumers to fintech services.…”
Section: Structural Model Evaluationmentioning
confidence: 99%
“…Subjective norms are a person's opinions about the beliefs of others, such as parents, siblings, and friends, that might influence whether or not a person engages in the behaviour being examined (Dharmawan et al, 2021). Subjective norms can be an interest in cash waqf because of the motivation for someone involved to do waqf.…”
Section: Introductionmentioning
confidence: 99%